1979
DOI: 10.1099/0022-1317-42-3-467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interferon on Murine Leukaemia Virus Infection. IV. Formation of Non-infectious Virus in Chronically Infected Cells

Abstract: SUMMARYInterferon (I5O units/ml) was used to treat SCq and AKR-2B cells which were chronically infected with murine leukaemia virus (MuLV). This led to a Ioo-fold decrease in the amount of infectious virus released into the medium and a Io-fold decrease in the number of virus particles measured by the virion-associated reverse transcriptase assay. However, there was little change in the amount of cellassociated infectious virus, though nearly twice as many cell-associated virions were counted in electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…HIV-1 virions assembled in IFN-treated T cells show a low infectivity, accumulate at the plasma membrane, and have altered morphogenesis (29)(30)(31). Similar defects were seen in IFN-treated cells infected with murine leukemia virus (32). We have shown that IFN-␣-and IFN-␤-mediated inhibition correlates with the induction of ISG15 (33).…”
supporting
confidence: 51%
“…HIV-1 virions assembled in IFN-treated T cells show a low infectivity, accumulate at the plasma membrane, and have altered morphogenesis (29)(30)(31). Similar defects were seen in IFN-treated cells infected with murine leukemia virus (32). We have shown that IFN-␣-and IFN-␤-mediated inhibition correlates with the induction of ISG15 (33).…”
supporting
confidence: 51%
“…An alternative possibility is that the vacuolar virions are a result of self phagocytosis by the cells of virus particles which are still bound to their own surface. The higher number of vacuolar virions found in IFN-treated cells does not contradict this possibility since several studies (Billiau et al, 1976;Chang & Friedman, 1977;Pitha et al, 1979b) have illustrated an accumulation of membrane-bound virions in IFN-treated cells. However, although this possible mechanism cannot be totally excluded, it seems rather unlikely, because careful analysis of many sections of IFN-treated and untreated cells revealed that virions bound to the cell surface are quite rare in our system.…”
Section: Accumulation Of Vacuolar Virions In Ifn-treated Cellsmentioning
confidence: 74%
“…Interferon-a (IFN-a) is thought to affect this budding process as well as several late events in the replicative cycle, and this agent is active against HIV in vitro during acute infection (85). 1538 Studies of murine retroviruses indicate that interferons predominantly affect the late stages of virion release from the plasma membrane of chronically infected cells (86). Indeed, IFN-a suppresses the production or release of HIV virions in chronically infected cells, but has no effect on the amount ofcell-associated viral proteins (87).…”
Section: The Budding Processmentioning
confidence: 99%